Reduction Sensitive Polymers Delivering Cationic Platinum Drugs as STING Agonists for Enhanced Chemo‐Immunotherapy. (21st August 2022) - Zhang, Lingpu; Shang, Kun; Li, Xiaomin; Shen, Meifang; Lu, Sheng; Tang, Dongsheng; Han, Hongbin; Yu, Yingjie
Abstract: STING agonists have made great progress in tumor immunotherapy. However, the inherent instability and low bioavailability have limited their wide applications. Herein, a reduction sensitive polymer with pair‐wised carboxyl groups that further encapsulate a cationic phenanthriplatin drug (PhenPt) as STING agonists into nanoparticles (PhenPt NPs) via electrostatic interactions is designed. PhenPt NP can release PhenPt in cancer cells, which then induce DNA damage, activate the STING signaling pathway, stimulate innate and adaptive immune responses, and improve the chemo‐immunotherapy efficacy. In vitro, for the first time it is found that PhenPt NP can activate cGAS‐STING pathway. Further genome‐wide RNA‐sequencing reveals that DNA replication, mismatch repair, homologous recombination, and other gene repair‐related pathways are involved. In vivo, PhenPt NP are found to completely inhibit the tumor growth, thereby shifting the tumor microenvironment from immunosuppressive to immunostimulatory phenotype, and boosting antitumor immune responses for long‐term immunity. In addition, PhenPt NP combined with checkpoint blockade therapy (a‐PD‐L1) can elicit long‐term immune response on both primary and distant tumors by activating the cGAS‐STING pathway. Overall, this nano‐delivery system with cationic chemotherapeutic drugs can greatly enhance DNA damage and activate immunity, hence providing a promising strategy for enhanced chemo‐immunotherapy. Abstract : Phenanthriplatin drug (PhenPt) is encapsulated with a reduction sensitive polymer to form PhenPt NP. Such PhenPt NP  act as STING agonists to convert "cold tumor" into "hot tumor", which greatly enhances the efficacy of chemo‐immunotherapy. Furthermore, the combination of PhenPt NP with checkpoint blockade therapy (a‐PD‐L1) elicits long‐term immune response on both primary and distant tumors by activating cGAS‐STING pathway.